Description of Eretmocerus cocois sp. n. (Hymenoptera: Chalcidoidea), a parasitoid of Aleurotrachelus atratus (Hemiptera: Aleyrodidae) on the coconut palm - Delvare, Gérard; Genson, Gwenaelle; Borowiec, Nicolas; Étienne, Jean; Karimé, Anli-Liochouroutu Abdoul; Beaudoin-Ollivier, Liochouroutu (Zootaxa, 2008)
Eretmocerus cocois Delvare sp. n. (Hymenoptera, Chalcidoidea) is described and illustrated. The adults emerge from fourth instar larvae of Aleurotrachelus atratus Hempel (Hemiptera, Aleyrodidae) which presently heavily infests the coconut plantations in Comoros Islands. It is compared with E. pallidus Dozier a diagnosis of which is given, together with new illustrations and with two other Eretmocerus also reared from Aleurotrachelus nymphs. A lectotype is selected for E. pallidus.